PENGARUH FIRM SIZE, PROFITABILITY, DAN LEVERAGE TERHADAP INCOME SMOOTHING PADA PERUSAHAAN MANUFAKTUR SEKTOR CONSUMER GOODS YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2019-2021 - Yolanda Manuella; Jamaludin Iskak (Jurnal Paradigma Akuntansi, 2026)
This research was conducted with the aim of determining the effect of firm size, profitability, and leverage on income smoothing in consumer goods manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2019-2021 period. The sample selection in this study was carried out using a purposive sampling technique and obtained a total sample of 75 data. This study uses binary logistic regression analysis. The data obtained was processed using the Statistical Product and Service Solution (IBM SPSS) version 27.0 program. The results of this study indicate that firm size has no effect on income smoothing, profitability has a negative effect on income smoothing, and leverage has a positive effect on income smoothing.